Corrigendum to "Intercomparison of dose enhancement ratio and secondary electron spectra for gold nanoparticles irradiated by X-rays calculated using multiple Monte Carlo simulation codes" [Phys. Med. 69 (2020) 147–163]. (December 2020) - Li, W.B.; Beuve, M.; Di Maria, S.; Friedland, W.; Heide, B.; Klapproth, A.P.; Li, C.Y.; Poignant, F.; Rabus, H.; Rudek, B.; Schuemann, J.; Villagrasa, C.
Highlights: EURADOS organized an inter-code intercomparison of dose enhancement of gold nanoparticles irradiated by kVp X-ray spectra. Variations and uncertainties of dose enhancement are observed by using multiple Monte Carlo codes. This study gives a reference range of dose enhancement in simulating gold nanoparticles irradiated by x-ray spectra. This intercomparison improved the simulation performances by identifying differences in settings, scoring and analysis. Further inter-code intercomparisons ensure a high quality of dose assessment for gold nanoparticle-assisted radiotherapy.